Drug release from ordered mesoporous silicas - L. Doadrio, Antonio; J. Salinas, Antonio; M. Sánchez-Montero, José; Vallet-Regi, M. (Current Pharmaceutical Design, 2015)
The state-of-the-art in the investigation of drugs release from Silica-based ordered Mesoporous Materials (SMMs) is reviewed. First, the SMM systems used like host matrixes are described. Then, the model drugs studied until now, including their pharmacological action, structure and the mesoporous matrix employed for each drug, are comprehensively listed. Next, the factors influencing the release of drugs from SMMs and the strategies used to control the drug delivery, specially the chemical functionalization of the silica surface, are discussed. In addition, how all these factors were gathered in a kinetic equation that describes the drug release from the mesoporous matrixes is explained. The new application of molecular modeling and docking in the investigation of the drug delivery mechanisms from SMMs is also presented. Finally, the new approaches under investigation in this field are mentioned including the design of smart stimuli-responsive materials and other recent proposals for a future investigation.
Keywords: ordered mesoporous